Susana Torres Molina: La indagación del mundo femenino en su dramaturgia y dirección teatral - Cabrera, Eduardo (Latin American Theatre Review, 2002)
The purpose of this work is to analyze the use of the aesthetics of the theatre of the image by Susana Torres Molina in the feminine world of current Argentina. The content of the plays written and directed by Torres Molina is generally related to the world of women. The director represents such world by actresses and especially through their bodies. As playwright and director, Torres Molina’s interest focuses in what happens within the woman, exploring the nature of her world and reconstructing such experience. Men’s image does not materialize onto the stage but through the woman’s voice. Throughout the analysis of Torres Molina’s plays emerge her intention, not in presenting the man as oppressor, but in discussing the theme of woman’s awareness. (EC, in Spanish)